A COMPARISON OF EFFECTS OF DEXMEDETOMIDINE VERSUS MIDAZOLAM-FENTANYL ON POST-OPERATIVE RECOVERY, SEDATION, ANALGESIA AND HEMODYNAMIC PARAMETERS IN PATIENTS UNDERGOING MIDDLE EAR SURGERY UNDER LOCAL ANESTHESIA - Goyal, Abhinav; Bhutani, Garima; Singh, Meena; Sharma, Naveen; Rani, Seema; Saini, Rahul; Ahmed Makki, Mohd Fazal (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to compare the effects of dexmedetomidine versus midazolam-fentanyl on post-operative recovery, sedation, analgesia, and hemodynamic parameters in patients undergoing middle ear surgery under local anesthesia. Methods: Seventy-two patients were randomly divided into two equal groups - Group D (dexmedetomidine) and Group MF (midazolam and fentanyl). Intra operative heart rate, mean blood pressure, respiratory rate (RR), and SPO2 were recorded every 15 min for the 1st 30 min and then at every 30 min interval till the end of the surgery. In post-operative period, hemodynamic parameters, Aldrete score and pain were assessed at every 30 min till the patient was discharged from post anesthesia care unit (PACU). Post-operative sedation of the patient was checked at 1 h, 2 h, 4 h, and 8 h. Observations: Midazolam and fentanyl combination caused more fall in Aldrete scores as compared to dexmedetomidine initially, but readiness to discharge from PACU was similar in both the groups. Patients of MF group had significantly higher sedation scores at post op 2 h, but overall duration of sedation was similar in both the groups. Post-op pain was significantly more in MF group patients, as compared to dexmedetomidine patients at 1.5 h. More number of patients of MF group demanded rescue analgesia in PACU. Both group of drugs caused similar changes in hemodynamic parameters during surgery but in post-operative period, dexmedetomidine produced less decline in RR and oxygen saturation as compared to midazolam and fentanyl combination. Conclusion: The present study concluded that dexmedetomidine seems to be a better alternative to the combination of midazolam plus fentanyl sedation for patients undergoing middle ear surgeries done under local anesthesia due to better analgesia and lesser derangement of hemodynamic parameters in post-operative period.